Processes of localization and institutionalization of local managers in economic functions in Danish owned subsidiaries in Estonia, Latvia and Lithuania around the 21st century - Thomsen, Jeanette (Journal of Business Economics and Management, 2008)
This study identifies interplay between the localization processes and formal as well as informal institutions in a specific context. Particularly the changes over time in institutions and localization processes are in focus. A longitudinal study of institutional changes in local management has been conducted from 1997 to 2002 among local CEOs, chief accountants and production managers in a Danish SME, using mainly qualitative methods. Data have been compared to primary data from similar companies in Estonia, Latvia and Lithuania. The study has resulted in establishing a model for comparing interplay between localization processes in SMEs and the formal and informal institutions in different transition and post‐transition economies.First published online: 14 Oct 2010